Toby Goes to Catholic School: Gender Expression Human Rights, and Ontario Catholic School Board Policy - Airton, Lee; DesRochers, Jacob; Kirkup, Kyle; Herriot, Lindsay (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2022)
In this article, we share findings from an analysis of Ontario Catholic school board policy documents (N = 179) containing Canada’s newest human rights grounds: gender expression and gender identity. Our major finding may be unsurprising—that Ontario Catholic boards are generally not responding to Toby’s Act (passed in 2012) at the level of policy, as few boards have added these grounds in a way that enacts the spirit of that legislation. While this finding is likely unsurprising, our study also yielded findings that unsettle any facile binary of “Catholic boards/bad” and “public secular boards/good” in relation to gender diversity. We also leverage our findings to suggest a striking possibility for a vigorous and doctrinally-compatible embrace of gender expression protections in Catholic schools, if not gender identity protections. We argue that fear of gender expression protections may stem from an erroneous conflation of “gender expression” with “gender identity” when these are in fact separate grounds—a conflation that is also endemic within secular Ontario school board policy; this doubles as a conflation of gender expression with “transgender,” as the latter is unfailingly linked with gender identity human rights. We make a series of recommendations for policy, and a case for Catholic schools embracing their legal duty to provide a learning environment free from gender expression discrimination without doctrinal conflict and arguably with ample doctrinal support, so that students of all gender expressions can flourish regardless of whether they are or will come to know they are transgender.